(untitled) (Memorias Sifored - Encuentros Educación UAN, 2023)
Education in Colombia needs a transformation around the teaching processes that are currently evident. This is due to the fact that in the XXI century, teachers are still using traditional methods and practices to teach. Therefore, this qualitative research is developed, based on the hermeneutic paradigm, with a group of teachers interested in innovating their educational practice taking into account the curricular principle of interdisciplinarity, which had positive results since the participants found it useful and meaningful for their teaching practice and realized that through this principle they promote abilities, skills and knowledge, forming competent citizens with a holistic vision of the world.